Modeling Motor Vehicle Tax Revenue with a One-Time Payment Scheme: A Case Study of the Jombang Regional Government - Ramdhan Fazrianto Suwarman; Anik Tri Mulyani; Andi Daniah Pahrany (Economics and Digital Business Review, 2026)
This study examines the effectiveness of Motor Vehicle Tax (PKB) collection by comparing the annual payment system, with an average compliance rate of 83.57%, to a one-time lump-sum payment scheme. The analysis employs time value of money concepts and Discounted Cash Flow (DCF) to calculate present values, alongside the Weibull distribution to estimate vehicle lifespan. For the lump-sum scheme, an annuity model over a 20-year period, reflecting the average vehicle life, results in a one-time PKB payment of IDR 2,556,467.50 per vehicle. The model further simulates the addition of new vehicles and estimates for existing vehicles. Findings reveal that, under the annual system, projected PKB revenue over the next 20 years—assuming a switch to the lump-sum scheme in 2026—would total IDR 991.4 billion, with realized revenue at IDR 828.5 billion and potential losses of IDR 162.8 billion due to arrears. In contrast, the lump-sum scheme would yield both potential and realized revenues of IDR 1.38 trillion, with no projected losses as taxes are paid upfront. Simulations indicate annual system revenue leakage could reach IDR 530 billion if all vehicles are unregistered. The study concludes that a lump-sum payment system reduces annual tax losses, increases revenue certainty, and strengthens regional fiscal resilience.